Sleep-Disordered Breathing Is Associated with Metabolic Syndrome in Outpatients with Diabetes Mellitus Type 2. (18th April 2019) - Neumann, K.; Arzt, M.; Heid, I.; Böger, C.; Stadler, S.
Abstract : Background . Metabolic syndrome (MS) and sleep-disordered breathing (SDB) are highly prevalent in patients with diabetes mellitus type 2 (DM2). The present study examined whether there is an independent association between SDB and MS in a sample of outpatients with DM2. Methods . MS was determined in 679 patients of the DIACORE-SDB substudy, a study of outpatients with DM2. According to the National Cholesterol Education Program (NCEP) criteria, MS is defined by at least three of the following five criteria: waist circumference of >102 cm (men)/>88 cm (women), blood pressure of ≥130/85 mmHg, a fasting triglyceride level of >150 mg/dl, high-density lipoprotein (HDL) of <40 mg/dl (men)/<50 mg/dl (women), and a fasting glucose level of ≥110 mg/dl. The apnea-hypopnea index (AHI) was assessed with a 2-channel ambulatory monitoring device and used to define the severity of SDB (AHI < 15.0 : no/mild SDB; AHI 15.0-29.9: moderate SDB;AHI ≥ 30.0 : severe SDB). Results . 228 (34%) of the 679 participants (mean age 66 years, mean body mass index (BMI) 31.2 kg/m 2, and mean AHI 14/hour) had SDB. MS was significantly more frequent in patients with more severe SDB (no/mild SDB vs. moderate SDB vs. severe SDB: 72% vs. 79% vs. 85%, respectively, p = 0.038 ). Logistic regression analysis adjusted for sex, age, obesity (BMI ≥ 30 kg/m 2 ), and the HOMA index showed a significant association between the AHI and the presence of MS (OR95 % CI = 1.039 (1.011; 1.068);p = 0.007 ). Further, male sex, obesity, and the HOMA index were significantly associated with MS. Conclusion . SDB is significantly and independently associated with MS in outpatients with DM2.